Chapter La ricerca di uno schema concettuale e di una metodologia appropriati per affrontare le sfide generate dalla dinamica tecno-economica - Lombardi, Mauro (Studi e saggi, 2021)
In this chapter, first three traditional frames centered on innovation processes and innovative strategies are analyzed: Linear Model, National Innovation Systems, Evolutonary Approach to the analysis of economic processes. The reasons that lead us to seek a new conceptual frame, which we define adaptive strategic thinking on the basis of a theoretical and empirical literature, are explained.